Mekka in the Latter Part of the 19th Century by Christiaan Snouck Hurgronje: Historical Writing or Historical Sources? Mekka in the Latter Part of the 19th Century Karya Christiaan Snouck Hurgronje: Tulisan Sejarah atau Sumber Sejarah? - Nurhayati, Anifa; Haikal (Indonesian Journal of Islamic History and Culture, 2024)
The following paper aims to explore fundamental questions surrounding the status of the work of renowned orientalist Christiaan Snouck Hurgronje. Although the term "historical genre" naturally arises when reading Mekka in the Latter Part of the 19th Century, this article critically questions whether Hurgronje's work should be categorized as a historical narrative or as a historical source. Through further investigation, this paper elaborates on and reviews the background of the work, provides a broad description of the book's content, analyzes its writing characteristics, and then connects these to the concepts of 'historical writing' and 'historical sources.' Therefore, this article opens a discussion on the nature and purpose of Hurgronje's writings and their relevance as a contribution to understanding the history of Mecca in the late 19th century, including the development of Islamic historiography in Indonesia. The data collection for this paper is based on library research. A historical approach is applied to this study, reinforced by Berelson's Content Analysis theory.